Ensino religioso nas escolas municipais da Zona Norte de Curitiba - Deus, Valdir Cândido de (2010)
The training of teachers for the area of religious education is the object of this study. Through documentary analysis, analyzed how the Religious Education is taught today in municipal schools, through the new guidelines. The paper was prepared in three chapters. The first chapter deals with the legislation that gave the structure of religious education, spanning from Brazil colony until today. Providing elements to build a proposal that enables the Religious Education. The second chapter shows the training process for teachers of Religious Education and also the legislation for such a procedure, explaining the difficulties to the religious education insertion in the schools. Chapter three deals with the religious education in schools in the northern area of Curitiba. It was analized in a documentary form the ASSINTEC and their collaboration for the existence of Religious Education in schools. The survey provided the knowledge of the existence of standards for teaching religion in public schools contained in the pedagogical book: Ensino Religioso . The research reveals that the training process teachers, urgently needs to be done, because in that way will be passed to the students, the real meaning of citizenship, that will make participating citizens in the destiny of this nation.